What is the most effective exercise protocol to improve cardiovascular fitness in overweight and obese subjects? - Eliane Aparecida Castro; Ana Belén Peinado; Pedro Jose Benito; Mercedes Galindo; Marcela González-Gross; Rocío Cupeiro (Elsevier, 2017)
Background: Increased peak oxygen consumption (VO2peak) can reduce cardiovascular risks associated with obesity. Our aim was to analyze the effect of a weight loss program on cardiovascular fitness in overweight (W) and obese (O) subjects. Methods: One hundred and sixty-seven subjects (77 males and 90 females), aged 18-50 years, performed a modified Bruce protocol before (pre) and after (post) a weight loss program of 24 weeks. This program combined physical training (strength, S; endurance, E; combined strength + endurance, SE; or physical activity recommendation, PA) 3 times per week, with a 25%-30% caloric restriction diet. Results: VO2peak improved in overweight and obese males (pre and post values in L/min, respectively; W = 3.2 ± 0.6 vs. 3.7 ± 0.5, p < 0.001; O = 3.6 ± 0.6 vs. 3.8 ± 0.6, p = 0.013) as well as in overweight females (2.0 ± 0.3 vs. 2.3 ± 0.4, p < 0.001). VO2peak in the first ventilatory threshold (VT1) increased for all 4 interventions in males (p < 0.05), except for S in the obese group (1.6 ± 0.2 vs. 1.7 ± 0.3, p = 0.141). In females, it increased in E (0.9 ± 0.2 vs. 1.4 ± 0.3, p < 0.001), SE (0.9 ± 0.2 vs. 1.2 ± 0.4, p = 0.003), and PA (0.9 ± 0.1 vs. 1.2 ± 0.2, p = 0.006) in overweight groups. Time-to-exhaustion improved in all subjects except for females in PA group (15.7 ± 0.3 min vs. 15.9 ± 0.3 min, p = 0.495). Conclusion: Our results suggest that all methods, including the recommendation of physical activity, can improve cardiovascular fitness in overweight subjects and obese males.